Influencia de la música infantil en el desarrollo del vocabulario en los niños de educación inicial ii - Chalán Arévalo, Gladys Verónica (2018)
The objective of this investigation tried to determine the music influence in the development of the vocabulary, despite of the music benefits this is not applied correctly in the class room, this and other factors create children with limited vocabulary. Metodology: This investigation was growth explanatorily with the participation 25 of preschool children. Method : There was made an empirical study to know the influence , in the vocabulary. The used technic was the observatión. like instruments were an observatión sheet and check list, applying the educational ministery valoratión: I=starting, EP in process and A=Adquired, also controling the class plan. The step by step started whith the selection and elaboration of the song according to the learning and memorizing experience. after that connect the lyric whith, the rythm using claps with corporal movements. Also, we used instruments made of bottles to create rythm. Keywords: Vocabulary, development, influence, music.